2008
DOI: 10.1016/j.jacc.2007.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cardiac Death in Hemodialysis Patients by Myocardial Fatty Acid Imaging

Abstract: Severely impaired myocardial fatty acid metabolism, which might mainly reflect repetitive myocardial ischemia, can identify a high-risk group of cardiac death among hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 23 publications
1
68
0
Order By: Relevance
“…Among patients with a summed 123 I-BMIPP score of $12 event-free survival at 3 y was 61%, whereas for those with a summed 123 I-BMIPP score of ,12 event-free survival was 98%. When 123 I-BMIPP uptake (metabolism) was assessed in relation to regional thallium uptake (perfusion), indicating myocardial ischemia, the sensitivity and specificity of metabolism:perfusion mismatch for predicting cardiac death were 86% and 88%, respectively (52). These findings support the assertion that altered cardiac metabolism (indicating silent myocardial ischemia) is highly prevalent in ESRD patients and can identify the subgroup of patients who are at high-risk for cardiac death (53).…”
Section: Screening Asymptomatic Patientssupporting
confidence: 61%
See 2 more Smart Citations
“…Among patients with a summed 123 I-BMIPP score of $12 event-free survival at 3 y was 61%, whereas for those with a summed 123 I-BMIPP score of ,12 event-free survival was 98%. When 123 I-BMIPP uptake (metabolism) was assessed in relation to regional thallium uptake (perfusion), indicating myocardial ischemia, the sensitivity and specificity of metabolism:perfusion mismatch for predicting cardiac death were 86% and 88%, respectively (52). These findings support the assertion that altered cardiac metabolism (indicating silent myocardial ischemia) is highly prevalent in ESRD patients and can identify the subgroup of patients who are at high-risk for cardiac death (53).…”
Section: Screening Asymptomatic Patientssupporting
confidence: 61%
“…In a prospective study of 130 asymptomatic ESRD patients undergoing hemodialysis, significant coronary artery luminal narrowing ($75%) was present in 71% of ESRD patients (51). The same investigators subsequently examined the prognostic significance of reduced myocardial metabolism with 123 I-BMIPP in conjunction with perfusion abnormalities assessed with thallium in ESRD patients without prior myocardial infarction (52). Among the 318 asymptomatic hemodialysis patients who were prospectively enrolled in the study, 50 (16%) died of cardiac events during a mean follow-up period of 3.6 6 1.0 y.…”
Section: Screening Asymptomatic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nishimura et al reported that BMIPP summed defect scores (BMDS) could stratify a poor prognosis for cardiac or sudden death based on a cutoff value of 12 among patients on HD, including 33% of those with diabetic nephropathy; the cardiac death rates of patients with a lower BMDS over 5 years was quite low. 20 Another study at the same institute revealed that lower BMIPP uptake and insulin resistance may be associated with cardiac death among HD patients, even without obstructive coronary artery disease. 21 The present findings contradict these results, perhaps because the characteristics of the patients differed; that is, the prevalence of cardiac events and mortality is generally higher in patients on HD.…”
Section: Discussionmentioning
confidence: 99%
“…3, 4 Recently, a multicenter prospective cohort study in Japan, the B-SAFE (BMIPP single-photon emission computed tomography [SPECT] Analysis for Decreasing Cardiac Events he prevalence and incidence of end-stage kidney disease (ESKD) have continued to increase worldwide, and Japan is known to have the highest prevalence of ESKD in the world. In 2009, there were 67,000 predialysis chronic kidney disease stage G5 patients, 37,365 patients introduced to dialysis therapy, and 101 patients who received pre-emptive renal transplantation.…”
Section: Article P 153mentioning
confidence: 99%